Meningkatkan Motivasi Kewirausahaan Melalui Pendekatan Dominansi Dalam Peer Learning - Dwi Rorin Mauludin Insana; Yuliana Ambarsari (SAP (Susunan Artikel Pendidikan), 2018)
A working group is likely to have a large influence on strengthening student motivation for entrepreneurship development. In a work group, there must be participants who are dominant or less dominant, where members from one another support and motivate each other for the success of the final results of group work. It is inspiring for researchers to find out whether the effects in working group dominance models can boost their level of motivation in entrepreneurship. This study aims to analyze the results of dominance by peer learning on other students in the work group and see the effect of peer learning on entrepreneurial motivation. The research method used was a quantitative method of experimentation with One group pre test ? post test with a sample of 60 students in the 8th semester of the English Language Education program. Based on the research data presented, it can be seen in general that the values of entrepreneurial motivation and in each group tends to increase after peer learning. The average value of the pretest is 67.1 while the posttest value is 77, then after the t test (t-test) is obtained the value of tcount, 6.967> ttable, 2,000, this means that the research hypothesis has the influence of the use of peer learning on accepted student entrepreneurial motivation . The conclusion of this study is that there is a significant effect of peer learning on the motivation of student entrepreneurship with the best increase in motivation is the mixed group